Short-term exposure to indoor PM2.5 in office buildings and cognitive performance in adults: An intervention study. (1st April 2023) - Zhou, Jiaxu; Wang, Hong; Huebner, Gesche; Zeng, Yu; Pei, Zhichao; Ucci, Marcella
Abstract: Impacts of exposure to particulate matter can be wide-ranging, with some evidence suggesting potential impacts on nervous system, cognition, and productivity. However, most evidence to date addresses ambient exposure and chronic outcomes with limited research on indoor short-term exposure to PM2.5 and cognitive performance. Hence, the aim of this study was to evaluate if there is a relationship between short-term exposure to indoor PM2.5 within the workplace context and cognitive performance in adults. A randomized single-blind cross-over trial was conducted in an urban mixed-mode ventilated office in Beijing (China). Sixty eligible employees participated in the study and fifty-five valid responses were obtained. Cognitive performance was assessed with a validated neurological battery test during intervention and control conditions. Portable air purifiers were placed on the subjects' workstations and used in the intervention condition to control PM2.5 levels at the subjects' breathing zone whereas in the control condition, the air purifiers were present but switched off. Average PM2.5 levels were respectively 18.0 μg/m³ and 3.7 μg/m³ in the control and intervention condition. In each condition, cognitive performance testing started five to 7 h after arriving in the office. The results showed office workers had significantly better performance for 9 out of the 16 cognitive skills during the intervention, compared to the control condition, with the most consistent effect in the memory domain. This study adds evidence that elevated PM2.5 levels can detrimentally affect cognitive performance even during short-term indoor exposure. Further research is needed on the potential impact of other air pollutants, including ultrafine particles, and on the possible role of sound and air movement from the air purifiers. Highlights: Study evaluated short-term exposure to indoor PM2.5 and cognitive performance. Randomized single-blind cross-over trial in an office building (Beijing, China). Desk-based air purifiers as intervention. Elevated indoor PM2.5 levels affect some cognitive performance domains in adults. Future research is needed to investigate the role of ultrafine particle exposure, sound, and air flows on cognitive effects.